Evaluation of various tuning rules for tuning of level process control / Muizzuddin Maslan - Maslan, Muizzuddin (2023)
This research will study the effects of various tuning rules on the level process control. The tuning rules being studied are Ziegler-Nichols, Cohen-Coon, and Takahashi tuning rules. Level process control is the process of maintaining a desired liquid level in a tank or vessel by adjusting the flow of liquid into or out of the tank. The basic components of a level control system include a sensor to measure the level of liquid in the tank, a controller to compare the measured level to the desired setpoint, and an actuator to adjust the flow of liquid into or out of the tank. Tuning a level control system involves adjusting the parameters of the controller to achieve the desired performance. There are several different methods for tuning a level control system, including manual tuning, trial-and-error tuning, and automatic tuning. Manual tuning involves adjusting the controller's parameters based on the operator's experience and knowledge. This method is often used when the process is not well understood or when the process is in a steady state. Trial-and-error tuning involves adjusting the controller's parameters and observing the process response. This method can be used when the process is well understood, but it can be time-consuming and may not result in the best performance. The Ziegler-Nichols tuning rule is a popular method that uses process oscillations to determine the controller's parameters. The process is first run in open-loop, and the controller's parameters are adjusted based on the amplitude and period of the oscillations. In summary, level process control is the process of maintaining a desired liquid level in a tank or vessel by adjusting the flow of liquid into or out of the tank. Tuning a level control system involves adjusting the parameters of the controller to achieve the desired performance. There are several different methods for tuning a level control system, including manual tuning, trial-and-error tuning, and automatic tuning. By the end of this study, it had been decided that Takahashi tuning rules are the most suitable and have the best performance for tuning of Level Process Control.